Pembuatan Pupuk Organik Cair Dari Limbah Kulit Bawang Merah - Halimatussa’diyah, Enni; Silvia, Cindy; Ananda, Uci Fitri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Onion production has expanded among the community from year to year, the large amount of shallot skin waste can bring new problems that can affect environmental pollution if not handled immediately. The purpose of this research is to provide knowledge about the manufacture of liquid organic fertilizer from shallot skin waste. Compounds found in shallot skin contribute to soil fertility and have a positive impact on plants. The research methodology used is an experimental approach by applying yourself how to make liquid organic fertilizer from leftover shallot skins. The research findings show that the remaining shallot skins can be used as liquid organic fertilizer which has many benefits for plant growth. In line with previous findings that have been made, said that chili plants can utilize liquid organic fertilizer made from onion peel application to grow faster. In addition to chili plants, liquid organic fertilizer can also help grow okra, mustard greens, spinach, tomatoes, and ornamental plants. Keywords: Organic Fertilizer, Shallot Skin Waste